ІNFORMATION SUPPORT OF SCIENCE AT UNIVERSITIES IN THE MODERN EDUCATIONAL SPHERE OF UKRAINE - Lesyuk, Olha V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The intellectualization factors of modern space in the Ukraine are consistently described and justified. The main organizational centers among them are universities. Combination of basic science and scientific practices in higher education provide the creation of new social intelligence of the nation. The condition of the professionalization of modern higher education in Ukraine is its information support using international and national information resources.